Immigrants and Dissidents: Stoicism and Radical Political Action In Rome - Dinucci, Aldo; Rudolph, Kelli; Balieiro, Marcos; Whiting, Kai (Revista Archai, 2024)
This article is an attempt to clarify the relationship between the dissident position taken by the ancient Stoics in their social context and the courageous way in which they defended their political positions in adherence to their Stoic philosophical principles - positions which led many of them to exile and death during the Imperial Period (the third phase of Roman civilization, which extended from 27 BCE to 476 CE). We suggest that the marginalization of these groups, as well as the persecution of them, uniquely positions the Stoics both in their own time and in ours.